Sex-based metabolic and microbiota differences in roots and rhizosphere soils of dioecious papaya (Carica papaya L.) - Zhou, Yongmei; Pang, Ziqin; Yuan, Zhaonian; Fallah, Nyumah; Jia, Haifeng; Ming, Ray (Frontiers in Plant Science, 2022)
Dioecious plant species have a high genetic variation that is important for coping with or adapting to environmental stress through natural selection. Intensive studies have reported dimorphism morphism in morphology, physiology, as well as biotic and abiotic stress responses in dioecious plants. Here, we demonstrated the dimorphism of metabolic profile and the preference of some microorganisms in the roots and rhizosphere soils of male and female papaya. The metabolic composition of roots were significantly different between the males and females. Some sex hormones occurred in the differential metabolites in roots and rhizosphere soils. For example, testosterone was up-regulated in male papaya roots and rhizosphere soils, whereas norgestrel was up-regulated in the female papaya roots, indicating a possible balance in papaya roots to control the sexual differentiation. Plant hormones such as BRs, JAs, SA and GAs were also detected among the differential metabolites in the roots and rhizosphere soils of dioecious papaya. In addition, some metabolites that have medicinal values, such as ecliptasaponin A, crocin, berberine and sapindoside A were also expressed differentially between the two sexes. Numerous differential metabolites from the papaya roots were secreted in the soil, resulting in the differences in microbial community structure in the roots and rhizosphere soils. Some nitrogen-fixing bacteria such as Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium, Brevundimonas and Microvirga were enriched in the male papaya roots or rhizosphere soils. While Candidatus Solibacter and Tumebacillus, which utilize organic matters, were enriched in the roots or rhizosphere soils of the female papaya. Some differences in the fungi abundance were also observed in both male and female papaya roots. These findings uncovered the effect of sex types on the metabolic and microbiota differences in roots and rhizosphere soils in papaya and will lead to investigations of underlining genomic and molecular mechanisms.